EFFECTS OF TURBOCHARGING ON PERFORMANCE OF IC ENGINE: A REVIEW - Dilip Wamanrao Tathe; Prof. N.S. Bhalkikar (International Journal of Innovations in Engineering Research and Technology, 2021)
Turbochargers are used throughout the automotive industry as they can enhance the output of an internal combustion (IC) engine without the need to increase its cylinder capacity. The application of such a mechanical device enables automotive manufacturers to adopt smaller displacement engines, commonly known as “engine downsizing”. Historically, turbochargers were often used to increase the potential of an already powerful IC engine. The emphasis today is to provide a feasible engineering solution to manufacturing economics and “greener” road vehicles. It is because of these reasons that turbochargers are now becoming more and more popular in automobile applications. The aim of this paper is to provide a review on the techniques used in turbocharging to increase the engine output and reduce the exhaust emission levels